Analysis of the Sharia-based crypto-asset regulatory framework in the United Arab Emirates (UAE) and Bahrain - Sidiq, Muhamad Yusuf; Muliana, Siti (Journal of Islamic Law on Digital Economy and Business, 2025)
Purpose – This study analyzes the regulatory frameworks governing Shariah-compliant cryptocurrencies in the United Arab Emirates (UAE) and Bahrain, examining how these jurisdictions integrate Islamic principles into their crypto-asset regulations to foster legal digital financial markets. Methodology – Employing a qualitative approach, the research reviews secondary data sources, including official legal documents, the Shariah fatwas, government policies, and prior academic literature related to cryptocurrency regulation in the UAE and Bahrain. The comparative analysis highlights divergences and convergences in their legal and Shariah-conforming fintech ecosystems. Findings – The UAE and Bahrain have adopted progressive regulatory frameworks that permit cryptocurrency trading under explicit Shariah compliance conditions. The UAE’s Dubai Blockchain Strategy promotes blockchain adoption with robust oversight mechanisms, emphasizing transparency, consumer protection, and synergy with Islamic finance principles. Bahrain, among the first Arab nations to establish comprehensive crypto-asset regulations, mandates licensing, security standards, and Shariah audits by authorized bodies. Implications – Progressive and Shariah-aligned regulations in the UAE and Bahrain create fertile grounds for developing global standards for Islamic digital assets. Their frameworks enhance investor confidence, promote financial inclusion, and encourage the emergence of halal fintech products, such as digital sukuk and stablecoins. The findings suggest that other Muslim-majority countries can benefit from adopting similar adaptive, transparent, and Shariah-compliant regulatory schemes to integrate digital currencies into Islamic finance effectively. Originality – This study contributes original insights by focusing on the comparative analysis of two pioneering Arab states’ crypto-asset regulations through a Shariah lens, illuminating practical pathways toward a harmonized global Shariah standard for digital financial instruments.